Study on factors affecting vertical drilling bottom hole assembly performance and a new bottom hole assembly design method considering formation uncertainties - Xi, Chuanming; Zhang, Wei; Zhang, Nan; Chu, Hengzhi (Frontiers in Energy Research, 2022)
Drilling a deep vertical well at a low cost is very important for accelerating the exploration and development of oil and gas resources. Vertical drilling BHA design is the key to drill a vertical well, however the BHA design is still an art not science in some formation. In this paper, a new mechanical model of bent-housing motor BHA is established, a build rate prediction method considering formation properties is presented and a BHA design method considering formation uncertainties is proposed. The evaluation results of vertical drilling BHA show that formation dip, formation anisotropy and hole diameter expansion are the main factors affecting pendulum BHA performance, and formation dip, formation anisotropy, hole diameter expansion and the distance from the upper stabilizer to the bit are the main factors affecting bent-housing motor BHA performance. The case study of the proposed BHA design method demonstrates that hole diameter expansion is very important for vertical drilling BHA performance, and should be taken in to account during the design process. The models and method proposed in this paper is helpful in maintaining verticality and reduce drilling cost.